Computer Music Research Group - IME/USP Report for SBCM 2019 - Gorodscy, Fábio; Feulo, Guilherme; Figueiredo, Nicolas; Itaboraí, Paulo Vitor; Bodo, Roberto; Borges, Rodrigo; Moura, Shayenne (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2019: Anais do XVII Simpósio Brasileiro de Computação MusicalDO - 10.5753/sbcm.2019.10443, 2019)
The following report presents some of the ongoing projects that are taking place in the group’s laboratory. One of the noteable characteristics of this group is the extensive research spectrum, the plurality of research areas that are being studied by it’s members, such as Music Information Retrieval, Signal Processing and New Interfaces for Musical Expression.